2002
DOI: 10.1038/sj.ejcn.1601494
|View full text |Cite
|
Sign up to set email alerts
|

Cooking of meat and fish in Europe—results from the European Prospective Investigation into Cancer and Nutrition (EPIC)

Abstract: Objectives: There is epidemiologic evidence that the consumption of fried, grilled or barbecued meat and fish that are welldone or browned may be associated with an increased cancer risk. These high-temperature cooking methods are thought to be surrogates for mutagens and carcinogens produced in meat and fish, eg heterocyclic amines or polycyclic hydrocarbons. Since data on food cooking methods are scarce, the aim of this study was to describe the variation in meat and fish cooking methods in different parts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 40 publications
2
29
0
1
Order By: Relevance
“…To give a good estimates of the intake of HA or PAH, one would have to develop a questionnaire on cooking methods for fish and degree of browning that could be applied in all EPIC countries. 31 Since we found no association between fish and breast cancer for any of the countries, there is no reason to believe that the results would differ substantially by adjusting for these compounds.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…To give a good estimates of the intake of HA or PAH, one would have to develop a questionnaire on cooking methods for fish and degree of browning that could be applied in all EPIC countries. 31 Since we found no association between fish and breast cancer for any of the countries, there is no reason to believe that the results would differ substantially by adjusting for these compounds.…”
Section: Discussionmentioning
confidence: 70%
“…Heterocyclic amines (HA) and polycyclic aromatic hydrocarbons (PAH) formed during preparation of the fish at high temperatures may be one of the reasons. Rohrmann et al, 31 studied the different preparation methods for meat and fish in the 24-HDR in EPIC. They found that hightemperature cooking methods were more often used in northern Europe and less often used in the EPIC cohorts of France, northern Italy, Greece and southern Spain.…”
Section: Discussionmentioning
confidence: 99%
“…However, estimates of the use of cooking methods associated with the highest levels of PAH, such as barbecuing (34) , are relatively low (1 %) in the Spanish population (35) . We calculated a weighted mean of BaP and total PAH for meat items based on the proportions of use of different cooking methods in the Spanish population estimated in the European Prospective Investigation into Cancer and Nutrition study (35) . The strength of the present study is that we estimated the intake of dietary PAH based on concentrations in individual foods, which enabled us to report the intake for fairly refined food subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…These so-called 'possibly hazardous cooking methods' (HCM) include barbecuing, frying and grilling. A detailed description of the use of cooking methods for the preparation of meat and fish was given elsewhere 27 . Due to differences in the extent of mis-(under-)reporting between centres 28 , all results were adjusted for total energy intake (continuous variable).…”
Section: Dietary Assessmentmentioning
confidence: 99%